MATERIAL CHARACTERICS TRADITIONAL FABRICS ATLAS AND ADRAS - Berdimbetova, Akzharkin Dzhumakhanovna (SCIENCE and SOCIETY, 2026)
The article examines the materials science characteristics of atlas and adras, showing that their structure and composition determine differences in physical and performance properties, and concludes that they are significant as traditional and environmentally friendly fabrics in the modern textile industry.
Keywords: atlas; adras; materials science; textiles; natural fibers; silk; cotton; hygroscopicity; mechanical properties; fabric structure; traditional fabrics of Uzbekistan